Clinical Experience of Yan Changhong in the Treatment of Herpes Zoster by Modified Da Qing Ye Tang with Bloodletting and Cupping at the Ashi Acupoint - He, Yuxuan; Zhao, Tenglu; Yan, Changhong (Journal of Contemporary Medical Practice, 2024)
Prof. Yan Changhong has been practicing medicine for dozens of years, with rich clinical experience, and specialized in the treatment of herpes zoster (HZ) using traditional Chinese medicine (TCM) therapy with obvious clinical effects. He believes that "poison" "fire" "dampness" "deficiency" and "blood stasis" are the main causes of HZ, and that clearing heat and removing toxins, strengthening the spleen and resolving dampness, and benefiting the vital energy and nourishing the blood are the main therapeutic methods of HZ. This article will summarize the clinical experience of Prof. Yan Changhong in the treatment of HZ by using modified Da Qing Ye Tang, acupuncture and bloodletting therapy at Ashi point combined with cupping, which is aimed at providing a new way of thinking for the treatment of HZ.